1999
DOI: 10.1097/00003246-199903000-00045
|View full text |Cite
|
Sign up to set email alerts
|

Volume of ventricular blood is an important determinant of outcome in supratentorial intracerebral hemorrhage

Abstract: Volume of intraventricular hemorrhage is an important determinant of outcome in supratentorial intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
266
3
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(296 citation statements)
references
References 22 publications
16
266
3
11
Order By: Relevance
“…Intraventricular blood is associated with a high mortality rate. 123 Ventriculostomy, rather than fiberoptic ICP devices, should be used in patients with hydrocephalus or intraventricular hemorrhage (Fig. 8).…”
Section: Neurosurg Focus / Volume 15 / October 2003mentioning
confidence: 99%
“…Intraventricular blood is associated with a high mortality rate. 123 Ventriculostomy, rather than fiberoptic ICP devices, should be used in patients with hydrocephalus or intraventricular hemorrhage (Fig. 8).…”
Section: Neurosurg Focus / Volume 15 / October 2003mentioning
confidence: 99%
“…Chung et al demonstrated that the mortality was 81% when thalamic hemorrhage presented the entire area of the thalamus: global type 13 . The volume of ventricular blood is an important determinant of outcome in supratentorial intracerebral hemorrhage, as shown by Tuhrim et al 14 .…”
Section: Discussionmentioning
confidence: 89%
“…In these studies, IVH tends to occur in patients with larger parenchymal hemorrhages, which is itself of adverse prognostic significance. Tuhrim et al (4) suggested that the volume of intraventricular blood is an independent predictor of outcome and a more important contributor to mortality after ICH than the mere presence of an IVH. We did not evaluate the volume of IVH, but the rate of IVH is significantly higher in patients with contrast extravasation, as compared to patients without extravasation.…”
Section: Discussionmentioning
confidence: 99%